The Equatorial Mode. A new regional and global perspective from the 70’s - García-Serrano, Javier; Rodríguez-Fonseca, Belén; Polo, Irene; Losada, Teresa; Mohíno, Elsa (Física de la Tierra, 2010)
The Equatorial Mode, also called Atlantic Niño, is the leading mode of the Tropical Atlantic Variability, explaining a high percentage of the anomalous boreal summer rainfall over the coast of the Gulf of Guinea. The evolution of the sea surface temperature anomalies associated with this mode from the 70’s show a starting point in the Santa Helena High Pressure System and in the related alongshore winds in the Angola/Benguela coast. The development of the mode is associated with a Bjierknes feedback mechanism, and the surface heat fluxes help to restore the surface temperatures. This mode, apart from having an important impact on the boreal summer West African Monsoon, is an important agent of extratropical teleconnections in association with the weakening of the mode from the end of summer to the next winter. From the 1970’s the origin, development and damping of the Equatorial Mode or Atlantic Niño leads the development of a Pacific La Niña through changes in the zonal Walker circulation. There are lot of references reporting a climate shift in the last decades of the XX century, not only in the Pacific but also in the rest of the globe. The cause of these changes and its relation to the Equatorial mode is a debated topic that does not rule out the role of the natural climate variability or the anthropogenic influence.